Multichannel Reaction of α‐Bromoenones with 1, 2‐Diamines: Synthesis of 1, 4‐Diazabicyclo[4.1.0]hept‐4‐enes by Reaction with N‐Unsubstituted 1, 2‐Diamines. Issue 8 (18th February 2016) - Muzalevskiy, Vasily M.; Rulev, Alexander Yu.; Kondrashov, Evgeniy V.; Romanov, Alexey R.; Ushakov, Igor A.; Chertkov, Vyacheslav A.; Nenajdenko, Valentine G.
Abstract: The reaction of 2‐bromoenones with N ‐unsubstituted 1, 2‐diamines was studied. An easy access to 1, 4‐diazabicyclo[4.1.0]hept‐4‐enes was developed. The multistep mechanism of the reaction is discussed. Final conclusions on the influence of the structure of the starting 2‐bromoenones and 1, 2‐diamines on the direction of the reaction are established. Abstract : The reaction of 2‐bromoenones and 1, 2‐diamines led effectively to 1, 4‐diazabicyclo[4.1.0]hept‐4‐enes.